A European-Type Wage Equation from an American-Style Labor Market: Evidence from a Panel of Norwegian Manufacturing Industries in the 1930s - Gunnar Bardsen; Jurgen Doornik; Jan Tore Klovland (Norges Bank, 2004)
Using a newly constructed panel of manufacturing industry data for interwar Norway, we estimate a long-run wage curve for the 1930s that has all the modern features of being homogeneous in prices, proportional to productivity, and having an unemployment elasticity of -0.1. This result is more typical of contemporary European than U.S. wage equations, even if the labour market in interwar Norway possessed distinctively more 'American' features than those associated with present-day European welfare states. We also present some new Monte Carlo evidence on the properties of the estimators used.
hdl:11250/2498549
Keywords: E24; N24; 330; wages; depression; panel data; dynamics